Vitamin D Enhances Radiosensitivity of Colorectal Cancer by Reversing Epithelial-Mesenchymal Transition - Yu, Xinyue; Wang, Qian; Liu, Baocai; Zhang, Ning; Cheng, Guanghui (Frontiers in Cell and Developmental Biology, 2021)
Colorectal cancer (CRC) is often resistant to conventional therapies. Previous studies have reported the anticancer effects of vitamin D in several cancers, its role in radiotherapy (RT) remains unknown. We found that 1α, 25-dihydroxyvitamin D3 (VD3), the biologically active form of vitamin D, had antitumor effect on CRC and sensitized CRC cells to ionizing radiation (IR). VD3 demonstrated synergistic effect in combination with IR, which were detected by colony formation and cell proliferation assay. Radiosensitivity restoration induced by VD3 was associated with a series of phenotypes, including apoptosis, autophagy, and epithelial-mesenchymal transition (EMT). Using proteomics, “regulation of cell migration” and “cadherin” were found to be obviously enriched GO terms. Moreover, cystatin D and plasminogen activator inhibitor-1 (PAI-1), the differentially expressed proteins, were associated with EMT. Next, we confirmed the contributions of these two genes in enhancing IR sensitivity of CRC cells upon inhibition of EMT. As determined by proteomics, the mechanism underlying such sensitivity involved partially block of JAK/STAT3 signaling pathway. Furthermore, VD3 also elicited sensitization to RT in xenograft CRC models without additional toxicity. Our study revealed that VD3 was able to act in synergy with IR both in vitro and in vivo and could also confer radiosensitivity by regulating EMT, thereby providing a novel insight for elevating the efficacy of therapeutic regimens.